2022
DOI: 10.3390/jcm11206071
|View full text |Cite|
|
Sign up to set email alerts
|

Is Less Always More? A Prospective Two-Centre Study Addressing Clinical Outcomes in Leadless versus Transvenous Single-Chamber Pacemaker Recipients

Abstract: (1) Background: Leadless (LL) stimulation is perceived to lower surgical, vascular, and lead-related complications compared to transvenous (TV) pacemakers, yet controlled studies are lacking and real-life experience is non-conclusive. (2) Aim: To prospectively analyse survival and complication rates in leadless versus transvenous VVIR pacemakers. (3) Methods: Prospective analysis of mortality and complications in 344 consecutive VVIR TV and LL pacemaker recipients between June 2015 and May 2021. Indications fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…After approval studies [ 8 , 9 , 16 , 17 , 21 ] have analyzed the LPM implantation feasibility and outcomes, LPMs have shown an optimal safety and efficacy profile in terms of low and stable pacing thresholds (PTs), with a consistent performance in real-life settings as well [ 4 , 8 , 16 , 22 , 23 ]. In addition, compared to TV-PMs, LPMs have been shown to reduce complication rates and to be a feasible therapeutic alternative for selected groups of patients [ 24 , 25 ]. However, few data have been provided on the feasibility of LPM implantation in an emergency setting, which still represents an extremely common scenario in the current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…After approval studies [ 8 , 9 , 16 , 17 , 21 ] have analyzed the LPM implantation feasibility and outcomes, LPMs have shown an optimal safety and efficacy profile in terms of low and stable pacing thresholds (PTs), with a consistent performance in real-life settings as well [ 4 , 8 , 16 , 22 , 23 ]. In addition, compared to TV-PMs, LPMs have been shown to reduce complication rates and to be a feasible therapeutic alternative for selected groups of patients [ 24 , 25 ]. However, few data have been provided on the feasibility of LPM implantation in an emergency setting, which still represents an extremely common scenario in the current clinical practice.…”
Section: Discussionmentioning
confidence: 99%
“…However, a meta-analysis on four studies showed no difference in the incidences of any complications between LPMs and TPMs [ 22 ]. Moreover, in a prospective analysis, no significant difference at an almost 2 year complication rate was observed between LPMs and TPMs [ 23 ], which could be because the contemporary complication rate of TPMs is significantly lower than the historical one as a result of standard implantation procedures and improved techniques. However, a contemporary prospective propensity-matched analysis also demonstrated that the rate of complication in a TPM cohort was 4.9% vs. 0.9% in a LPM cohort, during 800 days of follow-up and after excluding the pacemaker advisory-related complications [ 24 ].…”
Section: Leadless Ventricular Pacemakersmentioning
confidence: 99%
“…Last, we excluded patients who received leadless pacemaker implantation. Previous studies demonstrated its safety and efficacy in comparison with transvenous single-chamber ventricular pacing [ 24 ] and in high-risk patients after transvenous lead extraction [ 25 ]. Further trials will be necessary to confirm our study results.…”
Section: Study Limitationsmentioning
confidence: 99%